2013
DOI: 10.1104/pp.113.217810
|View full text |Cite
|
Sign up to set email alerts
|

Salinity-Induced Calcium Signaling and Root Adaptation in Arabidopsis Require the Calcium Regulatory Protein Annexin1    

Abstract: Salinity (NaCl) stress impairs plant growth and inflicts severe crop losses. In roots, increasing extracellular NaCl causes Ca2+ influx to elevate cytosolic free Ca2+ ([Ca2+]cyt) as a second messenger for adaptive signaling. Amplification of the signal involves plasma membrane reduced nicotinamide adenine dinucleotide phosphate oxidase activation, with the resultant reactive oxygen species triggering Ca2+ influx. The genetic identities of the Ca2+-permeable channels involved in generating the [Ca2+]cyt signal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
137
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(141 citation statements)
references
References 48 publications
(108 reference statements)
3
137
0
1
Order By: Relevance
“…There are numerous reports documenting AtANN1 functions as a calcium-permeable channel-like protein in response to abiotic stress, but most of the data was obtained from patch clamp experiments of spheroplasts and protoplasts of root epidermal cells (23,24,34). Here, using an aequorin reporting system, we found AtANN1 and AtANN2 play a role in regulating the elevation of [Ca 2ϩ ] cyt induced by heat shock in whole seedlings.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…There are numerous reports documenting AtANN1 functions as a calcium-permeable channel-like protein in response to abiotic stress, but most of the data was obtained from patch clamp experiments of spheroplasts and protoplasts of root epidermal cells (23,24,34). Here, using an aequorin reporting system, we found AtANN1 and AtANN2 play a role in regulating the elevation of [Ca 2ϩ ] cyt induced by heat shock in whole seedlings.…”
Section: Discussionmentioning
confidence: 73%
“…Levels-Prior reports indicated that AtANN1 could function to increase the Ca 2ϩ permeability of plasma membranes during plant stress responses (23,24). In order to test whether heatinduced calcium transport is altered in AtANN1 loss-of-function mutants, we crossed the ann1-2 and ann1-2/ann2 mutants with transgenic plants expressing 35 (Fig.…”
Section: Suppressing the Expression Of Atann1 And Atann2 Inhibits Heamentioning
confidence: 99%
“…While it had been described that mutations in this chloroplast-localized gene resulted in retarded shoot growth (Vainonen et al, 2008), an involvement in root growth had not been demonstrated. However, calcium signaling has been implicated in the determination of root growth (Monshausen et al, 2011;Laohavisit et al, 2013). Given the data from our genome-wide association study, we hypothesized that this gene might be involved in root growth determination.…”
Section: Resultsmentioning
confidence: 98%
“…Although sensing of these cues is believed to take place at the membrane (Christmann et al, 2013), the respective sensors are not yet well defined (Kumar et al, 2013;Osakabe et al, 2013). After stress perception, a burst of reactive oxygen species mediated by NADPH oxidases (Chung et al, 2008) triggers an increase in cytosolic Ca 21 levels (Laohavisit et al, 2013) and the synthesis of the phytohormone abscisic acid (ABA) (Fujita et al, , 2009Umezawa et al, 2010;Huang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%